The Influence of Liquidity Capital Adequacy and Asset Quality on Financial Performance of People's Economy Banks in the Bogor Region from 2019 to 2023 - Minar Pardede; Acu Kusnandar; Deni Hamdani (Eduvest - Journal of Universal Studies, 2026)
This study aims to analyze the effect of capital adequacy, liquidity, and asset quality on financial performance at Bank ABC during the period 2019–2023. Financial performance is measured using the Return on Assets (ROA) indicator as a representation of bank profitability. The independent variables in this study consist of the Capital Adequacy Ratio (CAR) as an indicator of capital adequacy, Loan to Deposit Ratio (LDR) as an indicator of liquidity, and Non-Performing Loan (NPL) as an indicator of asset quality. The method used in this study is quantitative with a descriptive and verification approach. The data used are secondary data obtained from Bank Perkreditan Rakyat financial statements for five years, and data analysis uses multiple linear regression with the help of statistical software (SPSS). The results of the study show that, both partially and simultaneously, capital adequacy, liquidity, and asset quality have a significant effect on Bank ABC's financial performance. This finding indicates that managing these factors is very important to maintain and increase bank profitability.